Telogen Effluvium and Trichodynia in Different Severity Groups of Post COVID-19 Patients - Arjel, Abhishek; Pokhrel, Kumar (Journal of Nepalgunj Medical College, 2022)
Introduction: Telogen Effluvium is one of the most common form of diffuse non scarring hair loss, usually occurring three months after a stressful event causing hair shedding. Trichodynia is an imminent and frequent warning sign of Telogen Effluvium. Increasing cases of Telogen Effluvium during COVID-19 era has been found and it should be an alarming sign for a dermatologist and patients who have been infected by COVID-19 in the past. Aims: To study Telogen Effluvium in post COVID-19 patients, onset of Telogen Effluvium and occurrence of Trichodynia in different severity groups of COVID-19. Methods: This casual-comparative study was conducted from January 2021 to December 2021 in total of 52 Telogen Effluvium patients with confirmed recent COVID-19 disease visiting in outpatient department of Dermatology in Nepalgunj Medical College Teaching Hospital. Patient’s with physiological, psychosocial and other chronic illness known to trigger Telogen Effluvium were excluded. Hair pull test was done for diagnosing Telogen Effluvium. Results:The mean age of the study population was 31.0577±11.78 years. There was a female preponderance with 39 (75%). The mean onset of hair loss after COVID-19 infection was 10.05 weeks and was significantly earlier among the higher severity groups. Among the patients with Telogen Effluvium, 16 (30.80%) presented with trichodynia. Kruskal- Wallis test showed that with increase in severity of COVID-19, there was early onset of Telogen Effluvium associated hair loss and increase occurrence of trichodynia with p value of 0.000 for both variables. Conclusion:Telogen Effluvium is common in post COVID patients. Post-COVID Telogen Effluvium is more common in females. The onset of Telogen Effluvium is earlier and is more associated with trichodynia with the increase in severity of COVID-19 during their illness.